Developing Website-Based E-Learning System Using Prototyping Methods for the Surabaya City Civil Service Police Unit - Bariq Adyatma Adyatma; Ari Kurniawan (Universitas Negeri Surabaya, 2026)
This study aims to create a website-based e-learning system for the Surabaya City Public Order Agency (Satpol PP) to address the time and cost constraints of conventional training for 1,279 personnel. The research focused on the independent distribution of legal materials and operational procedures. The method used was iterative prototyping, encompassing the stages of needs analysis, design, implementation, and system testing. During the implementation process, the system was built using the Laravel framework and a MySQL database. The results of functional testing (Black Box Testing) demonstrated a 100% success rate for all 36 tested features. Furthermore, User Acceptance Test (UAT) on 18 respondents yielded a satisfaction score of 88.55%, placing the system in the